Synthesis of some new heterocyclic compounds derived from 4-(4-hydroxy-3-chlorophenyl) azoaceto phenone - Hawaiz, Farouq E.; K, Mohammed; Samad1; Aziz, Marlin Y. (Sulaimani Journal for Pure and Applied Sciences, 2015)
p-Aminoacetophenone underwent diazotization and coupling reaction with 2- chlorophenol to give a starting material 4-(4-hydroxy-3-chlorophenyl)azoacetophenone. The prepared starting material was benzylated with benzylbromide producing 4-[4- benzyloxy-3-chloro-phenyl]azoacetophenone. The later has been reacted with different substituted benzaldehydes affording a series of new chalcones. The newly synthesized chalcones were treated with hydrazine hydrate to form the desired molecules azobenzyloxy-pyrazoline derivatives. The spectrum measurements of FT-IR, 1H-NMR and 13C-NMR, confirmed the expected structures of the newly synthesized compounds.
Keywords: paminoacetophenone; diazotization; coupling reaction; azochalcones; azopyrazoline